Preliminary Phytochemical Evaluation Of Leaf Extracts Of Euphorbia Hirta, Syzygium Cumini Of Siddarabetta, Tumkur District, Karnataka - S. M. GOPINATH; C. K. RAKESH; C. K. RAKESH; G. M. ASHWINI; K. S. DAYANANDA (International Journal of Pharma and Bio Sciences, 2012)
Phytochemicals are secondary metabolites in one or more parts of the medicinal plants. These have the ability to produce a definite physiological action on the human body. Medicinal herbs are the local heritage with global importance. Medicinal herbs have curative properties due to the presence of various complex chemical substances of different composition which are found as secondary metabolites in one or more parts of the plants. Keeping this view in mind the present investigation was carried out in Syzygium cumini stem, bark and Euphorbia hirta plants collected from Siddarabetta, Tumkur district. Karnataka, India. Qualitative phytochemical analysis of these plants confirms the presence of various phytochemicals like alkaloids, flavonoids, tannins, saponins, terpenoids and Quinone. The bioactive compounds from different solvent extracts suspected of anti-diabetic properties.